A Semianalytical Solution of the Fractional Derivative Model and Its Application in Financial Market. (1st April 2018) - Song, Lina
Abstract : Fractional differential equation has been introduced to the financial theory, which presents new ideas and tools for the theoretical researches and the practical applications. In the work, an approximate semianalytical solution of the time-fractional European option pricing model is derived using the method of combining the enhanced technique of Adomian decomposition method with the finite difference method. And then the result is introduced in China's financial market. The work makes every effort to test the feasibility of the fractional derivative model in the actual financial market.